Technological change and industrial development : issues and opportunities - Moore, Frederick T. (Washington, D.C., U.S.A. : World Bank, 1983)
This paper discusses the importance of technological change in industrial development, issues on which further study is required, and directions for operational programs that could be effective in raising the level of technical capabilities in LDCs. It defines technological change as the provision of new information or knowledge that is used effectively in industrial operations, including management and labour, and has measurable effects on costs, product qualities, level of output, or sales. The first part of the paper considers principal issues in the relationship of technological change to growth and the substitution possibilities among factors, notably capital and labor. Part two contains discussions concerning programs that are under way, with particular reference to the experience with several kinds of specific projects that are being implemented, particularly in the engineering or capital goods industries. This part also contains suggestions of ways of extending operations, revising policies and institutional arrangements, and making them more effective in promoting technological capabilities in industry
Includes bibliographical references: p. 72-81.
oo 09/04/2019
Loans
Keywords: Technological innovations; Industrialization